Multidrug Resistance Protein-4 Influences Aspirin Toxicity in Human Cell Line. (27th September 2015) - Massimi, Isabella; Ciuffetta, Ambra; Temperilli, Flavia; Ferrandino, Francesca; Zicari, Alessandra; Pulcinelli, Fabio M.; Felli, Maria Pia
Abstract : Overexpression of efflux transporters, in human cells, is a mechanism of resistance to drug and also to chemotherapy. We found that multidrug resistance protein-4 (MRP4) overexpression has a role in reducing aspirin action in patients after bypass surgery and, very recently, we found that aspirin enhances platelet MRP4 levels through peroxisome proliferator activated receptor- α (PPAR α ). In the present paper, we verified whether exposure of human embryonic kidney-293 cells (Hek-293) to aspirin modifies MRP4 gene expression and its correlation with drug elimination and cell toxicity. We first investigated the effect of high-dose aspirin in Hek-293 and we showed that aspirin is able to increase cell toxicity dose-dependently. Furthermore, aspirin effects, induced at low dose, already enhance MRP4 gene expression. Based on these findings, we compared cell viability in Hek-293, after high-dose aspirin treatment, in MRP4 overexpressing cells, either after aspirin pretreatment or in MRP4 transfected cells; in both cases, a decrease of selective aspirin cell growth inhibition was observed, in comparison with the control cultures. Altogether, these data suggest that exposing cells to low nontoxic aspirin dosages can induce gene expression alterations that may lead to the efflux transporter protein overexpression, thus increasing cellular detoxification of aspirin.